up previous next
ideal

ideal generated by list

Syntax
ideal(g1: RINGELEM,...,gn: RINGELEM): IDEAL
ideal(L: LIST): IDEAL
ideal(R: RING, L: LIST): IDEAL

Description
The first form returns the ideal generated by g1,...gn . The second form returns the ideal generated by the polynomials in L (a bit more flexible than the first form). The third is the same as the second but works also if L = [] .

Example
/**/  use R ::= QQ[x,y,z];
/**/  I := ideal(x-y^2, x*y-z);
/**/  I;
ideal(-y^2 +x, x*y -z)

/**/  L := [x*y-z, x-y^2];
/**/  J := ideal(L);  -- same as ideal(R, L)
/**/  I = J;
true

/**/  ideal(R, []);
ideal()